Theoretical and Experimental Investigation of Tool Inclination Angle in Turning Operation - Ali Abbar Khleif; Farhad Mohammad Kushnaw (Engineering and Technology Journal, 2011)
This paper introduces a mathematical model to calculate the amount of tool inclination angle in turning operation depending on controlling the chip flow along the cutting edge, and to simplify the setting of this angle and the direct relation with nose setting distance, a model is achieved to calculate the setting nose distance instead of changing the inclination angle. Results conducted on a series of experiments by changing tool nose setting distance where most of the cutting conditions kept constant, except tool nose setting below and above the workpiece centre, and its effect of obtained surface roughness was measured at each step. Theoretical results for finishing turning operation, for depth of cut less than 1 mm, show that setting tool nose below the workpiece centre will be similar to that of setting positive angle of inclination. The main function of the derived model of the inclination angle is to make equal chip flow along the cutting edge and the chip will be cured far enough from the machined surface and therefore eliminate the chip and hence improve the workpiece surface roughness. The proposed theoretical model proved that in external turning with finishing operation the suggested inclination angle (λ) must have positive values, and the setting distance has a negative value. While in the experimental work, the workpiece surface finish has been improved when setting distance has negative value below the workpiece centre.